Efisiensi dan Efektivitas Perusahaan terhadap Pertumbuhan Laba (Studi pada Perusahaan Sektor Aneka Industri) - Nopiani Indah (LPPM Universitas Widya Dharma Pontianak, 2022)
Efficient and effective management can increase profits. This study aims to determine the effect of the efficiency and effectiveness of the company on profit growth, using the ratio of activity, solvency, and profitability. The study was conducted on various industrial sector companies with 185 data samples. The data used is secondary data in the form of financial reports through IDX and the company's website. The analysis technique with regression modeling results in the finding that activity has a role in profit growth, while solvency and profitability do not indicate that the profit is significant. Keywords: profit growth, efficiency, effectiveness, activity, solvency, profitabiity